Effectiveness of oral health education for paid caregivers of adults with intellectual disabilities: A systematic review - Mc Brien, Barry (My University, 2026)
It has been identified that people with intellectual disabilities tend to have disproportionately poor oral health. This article details a systematic review that aimed to evaluate the effectiveness of oral health educational interventions for paid caregivers of adults with intellectual disabilities. Seven studies were included in the review, involving a total of 322 caregivers. The review found that oral health educational interventions improved caregivers’ knowledge in the short term, but that their knowledge retention commonly declined within three months. Caregivers’ behavioural and attitudinal outcomes were inconsistent, with temporary improvements often reverting to baseline. Clinical outcomes were limited and inconsistent, with only one study showing a notable improvement in plaque scores, and another study finding no meaningful change in gingival inflammation. Future research should prioritise randomised controlled trials with longer follow-up periods, standardised outcome measures, and theory-informed designs that incorporate behavioural change frameworks.
PUBLISHED
Keywords: carers; education; learning disability; literature review; oral health; oral hygiene; patient outcomes; support staff; Inclusive Society; Intellectual Disability